Ecology of West Nile Virus in North America - William K. Reisen (Viruses, 2013)
The introduction, dispersal and establishment of West Nile virus in North America were reviewed, focusing on factors that may have enhanced receptivity and enabled the invasion process. The overwintering persistence of this tropical virus within temperate latitudes was unexpected, but was key in the transition from invasion to endemic establishment. The cascade of temporal events allowing sporadic amplification to outbreak levels was discussed within a future perspective.